Coming to care the work and family lives of workers caring for vulnerable children - Brannen, Julia 1944- (Policy Press, 2007)
This book provides fascinating insights into the factors that influence why people enter and leave care work, their motivations, understandings and experiences of their work and intersection of it with their family lives